Cost-benefit analysis of alternative vehicles in the Philippines using immediate and distant future scenarios. (May 2020) - Lopez, Neil Stephen; Soliman, Jimwell; Biona, Jose Bienvenido Manuel; Fulton, Lewis
Highlights: Societal benefits from private EVs and FCVs are at least 3× higher than others. In the immediate future, DHEVs are potentially beneficial for public transport. B20, M85 and Diesel are potentially beneficial for private car owners. Autonomous rideshared vehicles can have lower costs than privately-driven cars. Policy recommendations are provided for a transitioning economy. Abstract: Alternative vehicle technologies promise a sustainable future by reducing carbon emissions and pollution. However, their widespread adoption tends to be slow due to high costs and uncertainties in benefits. Using a life cycle-based approach, this study calculates ownership savings and societal benefits for various alternative vehicle technologies against their baseline vehicle technology (e.g. gasoline or diesel). The assessment is performed from a developing country context – in the Philippines. Furthermore, immediate and distant future scenarios are modeled. The immediate future scenario assesses costs and benefits if the shift is to happen now, while the distant future scenario considers the effect of widespread autonomous driving and ridesharing. The results of the study echo the significant societal benefits from electric- and fuel cell-powered vehicles found in literature, but they are hindered by high ownership costs. In the immediate future, the diesel hybrid electric vehicle can potentially have both positive societal and operational costs for public transportation. For a gasoline-powered private passenger car, a simple shift to diesel, 20% biodiesel or 85% methanol can be beneficial. In the distant future, it is expected that autonomous, rideshared vehicles can potentially lure people away from driving their own vehicles, because of lower costs per passenger-kilometer while sustaining the privacy and comfort of a private car.